2010
DOI: 10.1002/jpln.200900147
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional reference values for Opuntia ficusindica determined by means of the boundary‐line approach

Abstract: Optimum concentrations and/or sufficiency ranges of nutrients are useful for a correct diagnosis and improvement of nutrient status of cultivated plants. To develop boundary‐line approach (BLA) standards for Opuntia ficus‐indica L., a database of N, P, K, Ca, and Mg concentrations in 1‐year‐old cladodes and cladodes fresh‐matter yield was used. The BLA optimum concentrations (associated with estimated maximum yield) for O. ficus‐indica were: N = 13.1 g kg–1, P = 3.2 g kg–1, K = 44.4 g kg–1, Ca = 38.1 g kg–1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
1
26
1
2
Order By: Relevance
“…1 As for P, the highest values of MCh were observed in the classes 4 and 5 (0.4-1.7 g kg -1 ) ( Table 2). The upper limit of MCh is close to that of SR, although its LLi, far lower, coincide with the NCRIz (1.0 g kg -1 ) ( Table 3), which is three times lower than what was obtained from a soil with high P content, 40.5 mg dm -3 (Blanco-Macías et al, 2010). Thus, SR is considered more suitable for evaluating the nutritional status of 'Gigante' forage cactus pear for P than MCh, as the latter is a method that exhibits a low LLi, deficient class (Table 1).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…1 As for P, the highest values of MCh were observed in the classes 4 and 5 (0.4-1.7 g kg -1 ) ( Table 2). The upper limit of MCh is close to that of SR, although its LLi, far lower, coincide with the NCRIz (1.0 g kg -1 ) ( Table 3), which is three times lower than what was obtained from a soil with high P content, 40.5 mg dm -3 (Blanco-Macías et al, 2010). Thus, SR is considered more suitable for evaluating the nutritional status of 'Gigante' forage cactus pear for P than MCh, as the latter is a method that exhibits a low LLi, deficient class (Table 1).…”
Section: Resultssupporting
confidence: 59%
“…Sufficiency ranges and critical levels have been determined for forage cactus pear in Mexico (Blanco-Macías et al, 2010); though, it is necessary to look into the interactions between genotype, environment, and management under semiarid conditions of Bahia state. Therefore, we aimed to establish the sufficiency ranges of macronutrients in tissues of cladodes for the evaluation of the nutritional status of forage cactus pear.…”
mentioning
confidence: 99%
“…It was assumed that there is no strong correlation between f VPD and f temp , even though VPD was estimated based on temperature (Pleijel et al, 2002). These mathematical functions were parameterized using a boundary line technique, which was first introduced by Webb (1972), and has been widely used in plant and soil science models (Bhat and Sujatha, 2013;Blanco-Macías et al, 2010;Lewandowski and Schmidt, 2006;Topp et al, 2013;Vizcayno-Soto and Côte, 2004). It was based on the principle that biological materials have an upper response limit to a given variable (Imhoff et al, 2010).…”
Section: Stomatal Conductance Measurements and Modelingmentioning
confidence: 99%
“…Changes in crop management, such as population density, combination of spacings and doses of organic (Donato et al, 2014) or chemical fertilization can interfere with the use of radiation and nutritional status of the plant (Galizzi et al, 2004;Silva et al, 2012), with consequent increment in the photosynthetic rates, growth and yield (Blanco-Macías et al, 2010), and in the extraction/exportation of nutrients. Ramos et al (2011) concluded that the spacing influences phytomass production and rainfall use efficiency, and the increments are higher for increasing densities .…”
Section: Introductionmentioning
confidence: 99%